The role of emotional inhibitory control in specific internet addiction: an fMRI study - Dieter, Julia; Hoffmann, Sabine; Mier, Daniela; Reinhard, Iris; Beutel, Martin; Vollstädt-Klein, Sabine; Kiefer, Falk; Mann, Karl (Behavioural brain research, 2017)
Background: Addicts to specific internet applications involving communication features showed increased social anxiety, emotional competence deficits and impaired prefrontal-related inhibitory control. The dorsal Anterior Cingulate Cortex (dACC) likely plays an important role in cognitive control and negative affect (such as social exclusion, pain or anxiety). Aim: To assess (social) anxiety-related inhibitory control in specific internet addiction (addicted use of games and social networks) and its relation to altered dACC activation. Methods: N=44 controls and n=51 specific internet addicts completed an anxious words-based Affective Go/No-Go task (AGN). A subsample of n=23 healthy controls and n=25 specific internet addicts underwent functional Magnetic Resonance Imaging (fMRI) while completing an Emotional Stroop Task (EST) with socially anxious, positive, negative and neutral words. Subgroups of internet gaming and social network addicts were exploratively assessed. Psychometric measures of social anxiety, emotional competence and impulsivity were additionally explored. Results: Specific internet addicts showed higher impulsivity, social anxiety and reduced emotional competence. Between-group differences in AGN and EST behavioral measures were not detected. No group differences were found in the dACC, but explorative analyses revealed decreased left middle and superior temporal gyrus activation during interference of socially anxious words in internet gaming and relative to social network addicts. Conclusion: Given the function of the left middle temporal gyrus in the retrieval of words or expressions during communication, our findings give a first hint that social words might be less retrievable in the semantic storage of internet gaming addicts, possibly indicating deficiencies in handling speech in social situations.